A case of juvenile systemic sclerosis and congenital pulmonary airway malformation related mucinous adenocarcinoma of the lung: paraneoplastic syndrome or just a coincidence? - Aliyeva, Ayten; Barut, Kenan; Şahin, Sezgin; Köker, Oya; Haşlak, Fatih; Yıldız, Mehmet; Batur, Şebnem; Ocak, Süheyla; Adrovic, Amra; Kasapçopur, Özgür (The Turkish Journal of Pediatrics, 2022)
Background. Juvenile systemic sclerosis (JSS) is an extremely rarely seen auto-immune disease characterized by the increased fibrosis of skin and internal organs. Congenital pulmonary airway malformation (CPAM) is a developmental disorder of the lung, characterized by atypical cell hyperplasia which creates the ground for lung adenocarcinoma. In general, CPAM is diagnosed in early childhood, due to recurrent respiratory symptoms including cough, hemoptysis and respiratory infections. Although rare, there are some sporadic asymptomatic cases of CPAM that have been reported. We present a case with a coincidental presence of two rare diseases: JSS and CPAM. Case. An adolescent female patient was admitted to hospital due to clinical signs of JSS. During the followup, the patient had been diagnosed with cystic adenoid malformation of the lung complicated by mucinous adenocarcinoma. The patient was previously healthy with an unremarkable history, including lack of respiratory symptoms. Left inferior lobectomy was performed. Considering the small size of malignant loci, the total resection of the tumor and absence of any sign for metastasis disease, adjuvant therapy was not scheduled. We haven`t found a pediatric case of CPAM associated adenocarcinoma of the lung presented by signs of JSS in the literature. In this case, the clinical signs of JSS possibly represent part of the paraneoplastic syndrome related to adenocarcinoma of the lung. Conclusions. Internal organ involvement, including respiratory system, should not be omitted even in asymptomatic patients with JSS. Auto-antibody negativity represents a clue for the possible underlying condition. Further studies with a higher number of patients would reveal more relevant data.